A systematic review of reports of quality improvement for bronchopulmonary dysplasia. Issue 1 (February 2021) - Healy, H.; Croonen, L.E.E.; Onland, W.; van Kaam, A.H.; Gupta, M.
Abstract: Bronchopulmonary dysplasia (BPD) is the most common morbidity of preterm infants, and its incidence has not responded to research and intervention efforts to the same degree as other major morbidities associated with prematurity. The complexity of neonatal respiratory care as well as persistent inter-institutional variability in BPD rates suggest that BPD may be amenable to quality improvement (QI) efforts. We present a systematic review of QI for BPD in preterm infants. We identified 22 reports from single centers and seven from collaborative efforts published over the past two decades. In almost all of the reports, respiratory QI interventions successfully reduced BPD or other key respiratory measures, particularly for infants with birth weight over 1000 g. Several themes and lessons from existing reports may help inform future efforts in both research and QI to impact the burden of BPD.